EFFECTS OF BUERGER–ALLEN EXERCISE ON PERIPHERAL NEUROPATHY IN PATIENTS WITH TYPE 2 DIABETES MELLITUS: A CASE STUDY IN PRIMARY CARE (Proceedings OPTIMAL, 2026)
Chronic hyperglycemia in patients with diabetes mellitus can lead to peripheral neuropathy, thereby increasing the risk of diabetic foot ulcers, amputation, and diminished quality of life. Non-pharmacological interventions are needed to enhance blood circulation and alleviate the symptoms of peripheral neuropathy. One such intervention is the Buerger–Allen Exercise (BAE). This study aimed to examine the effect of BAE therapy on the improvement of peripheral neuropathy in patients with diabetes mellitus.A case study approach was applied involving two patients with diabetes mellitus diagnosed with peripheral neuropathy. Assessments were conducted before and after the intervention using the Neuropathy Screening Score (NSS) to evaluate foot sensitivity, the Neuropathy Deficit Score (NDS) to assess sensory and reflex function, and the Michigan Neuropathy Screening Instrument (MNSI) to examine distal plantar symmetry.The findings demonstrated a reduction in neuropathy severity in both participants following the BAE intervention. Improvements were observed in NSS, NDS, and MNSI scores, indicating enhanced sensation, reflex response, and peripheral circulation in the lower extremities. In conclusion, BAE therapy appears to be effective in improving peripheral neuropathy among patients with diabetes mellitus and may be recommended as a complementary nursing intervention within primary healthcare settings.